2016
DOI: 10.1128/aac.02793-15
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mechanisms of Tenofovir and Tenofovir Disoproxil Fumarate Cellular Transport and Implications for Topical Preexposure Prophylaxis

Abstract: Intravaginal rings releasing tenofovir (TFV) or its prodrug, tenofovir disoproxil fumarate (TDF), are being evaluated for HIV and herpes simplex virus (HSV) prevention. The current studies were designed to determine the mechanisms of drug accumulation in human vaginal and immune cells. The exposure of vaginal epithelial or T cells to equimolar concentrations of radiolabeled TDF resulted in over 10-fold higher intracellular drug levels than exposure to TFV. Permeability studies demonstrated that TDF, but not TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 46 publications
(50 reference statements)
1
45
1
Order By: Relevance
“…At steady state, the intracellular TFV-DP ratio was ∼61% in both human and macaque PBMCs [1013]. Even with TFV, which exhibits 10- to 100-fold lower cell uptake in vitro [18], our data suggest that TLC-ART101 enhanced intracellular TFV and TFV-DP drug concentrations in NHP PBMCs and LNMCs, and substantially enhanced exposure. Even after weight-based adjustments, TLC-ART101 still provided a several thousand-fold increase in intracellular drug exposure versus TDF or TAF.…”
Section: Discussionmentioning
confidence: 87%
“…At steady state, the intracellular TFV-DP ratio was ∼61% in both human and macaque PBMCs [1013]. Even with TFV, which exhibits 10- to 100-fold lower cell uptake in vitro [18], our data suggest that TLC-ART101 enhanced intracellular TFV and TFV-DP drug concentrations in NHP PBMCs and LNMCs, and substantially enhanced exposure. Even after weight-based adjustments, TLC-ART101 still provided a several thousand-fold increase in intracellular drug exposure versus TDF or TAF.…”
Section: Discussionmentioning
confidence: 87%
“…The efficacy of topical PrEP is impacted by tissue permeability, transport into and out of cells, metabolism, and stability in the complex and dynamic mucosal environment. We previously showed that TFV enters human female genital tract (FGT) epithelial and immune cells by endocytosis, reflecting little or no organic anion transporter (OAT) expression (8)(9)(10). In contrast, the prodrugs TFV disoproxil fumarate (TDF) and TFV alafenamide (TAF) passively diffuse into cells, where they are metabolized by intracellular enzymes to TFV (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that TFV enters human female genital tract (FGT) epithelial and immune cells by endocytosis, reflecting little or no organic anion transporter (OAT) expression (8)(9)(10). In contrast, the prodrugs TFV disoproxil fumarate (TDF) and TFV alafenamide (TAF) passively diffuse into cells, where they are metabolized by intracellular enzymes to TFV (10,11). The differences in transport mechanisms are reflected by their relative potency; TDF and TAF inhibit HIV-1 and HSV-2 in human cell or explant tissue and murine models at 100-fold lower concentrations than TFV (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Common side effects that are associated with TDF are new‐onset or worsening renal impairment, lactic acidosis from severe hepatomegaly, and decreases in bone mineral density . Following administration, TDF is hydrolyzed by carboxylesterases to tenofovir . Tenofovir is renally eliminated by a combination of glomerular filtration and active tubular secretion .…”
mentioning
confidence: 99%
“…9 Following administration, TDF is hydrolyzed by carboxylesterases to tenofovir. 10,11 Tenofovir is renally eliminated by a combination of glomerular filtration and active tubular secretion. 11,12 Tenofovir is a substrate of human organic anion transporter 1 (OAT1) and OAT3 but not of human organic cation transporter 2.…”
mentioning
confidence: 99%